Mexico's colonial and early postcolonial state-formation: A political-Marxist account - Armando Van Rankin-Anaya (América Latina en la Historia Económica, 2022)
This paper analyses the agrarian *hacienda* as the chief defining political-economic institution that shaped class composition and state formation of colonial and early postcolonial Mexico. Following the insightful theoretical framework of political Marxism, this article reviews the evolution of Mexican social property relations from the colonization (in the 16th century) to independence (in the 19th century) employing a novel methodology. Due to the highly historicist-oriented perspective of this neo-Marxist wisdom –and its concrete notion of capitalism as a property regime politically constructed– this paper argues that the agrarian hacienda was substantially precapitalist. This reexamination, in turn, challenges structural and pancapitalist accounts within neo-Marxist thought such as Wallerstein’s world-system theory that argues conversely: that European colonialism in the Americas was capitalist. This work aims to expand the application of political Marxism literature to the Latin American context.